ANALISIS KEMAMPUAN MEMBACA DAN BERHITUNG SISWA KELAS II SD NEGERI 271 PALLAE - Malik, Abdul; Kaddas, Badruddin; Nurdiansyah, Erwin; Erniati, Erniati; Jumriati, Jumriati (ALENA : Journal of Elementary Education, 2023)
The problem in this research is the students' low reading and numeracy skills, which are formulated as follows: 1) How is the application of reading in the campus teaching program to students? 2) How is the application of the campus teaching numeracy program to students? This study uses a type of qualitative research. When the research was carried out from March to June 2022 at SD Negeri 271 Pallae for class II students. The instruments used in this study were observation, interviews and documentation. The data analysis technique used is the triangulation method. The results of the research provide solutions and assistance in teaching class II students by providing reading textbooks that are available every time we enter. Likewise in terms of arithmetic, we try to be more active in the class, especially in media jam learning by trying to approach each student so that they feel happy in learning. Another solution that we have done is to form additional hours for students, with the achievement that all students can read properly and correctly, no longer embarrassed when asked to read in front of the class, always focus on the teacher who teaches in class, and all students too already able to memorize addition and subtraction and can remember all the learning material as evidenced when they do the semester final exams.